The Effect of Instagram’s E-WOM on Netflix’s Brand Image and Subscription Decision - Luk Lukul Hamidah; Melvina Oktaviani; Lestari Nurhajati (Jurnal Audience: Jurnal Ilmu Komunikasi, 2021)
Abstract The video-on-demand (VoD) business in Indonesia is currently proliferating, such as Netflix that is also available in 190 countries. Netflix began to enter the Indonesian market in 2016, and the subscribers keepincreasing, with only 100,000 subscribers in 2017 and raised to 906,810 subscribers in 2020. This controversy due to its content and age categorization, Netflix’s subscribers grow unaffected. The role of Instagram’s electronic word-of-mouth (e-WOM) has a significant influence on the marketing of a business, including Netflix. In this study, the theory of Elaboration Likelihood Model (ELM) was employed to analyze the influence of Instagram’s e-WOM on brand image and subscription decision to Netflix. A total of 120 questionnaires was distributed across the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi), and the resulted dataset was quantitatively analyzed. This research also used path analysis to explore the direct and indirect effect of e-WOM on subscription decisions through brand image. The results showed that brand image positively and significantly strengthens the influence of eWOM on subscription decisions.Keywords: brand image; e-WOM; Instagram; Netflix, subscription decision Abstrak Bisnis video on demand (VoD) di Indonesia seperti Netflix memasuki pasar Indonesia pada tahun 2016, dan pelanggannya terus meningkat, berawal dari 100.000 pelanggan pada tahun 2017 dan meningkat menjadi 906.810 pelanggan pada tahun 2020. Di tengah kontroversi yang terus berlanjut karena kategorisasi konten dan usia, pelanggan Netflix tumbuh tidak terpengaruh. Peran electronic word-of-mouth (e-WOM), Instagram memiliki pengaruh yang signifikan terhadap pemasaran suatu bisnis, termasuk Netflix. Teori Elaboration Likelihood Model (ELM) digunakan untuk menganalisis pengaruh e-WOM Instagram terhadap citra merek dan keputusan berlangganan Netflix. Kuesioner disebarkan di seluruh wilayah Jabodetabek (Jakarta, Bogor, Depok, Tangerang, dan Bekasi) pada 120 responden. Data dianalisis secara kuantitatif dan menggunakan analisis jalur untuk mengeksplorasi pengaruh langsung dan tidak langsung e-WOM terhadap keputusan berlangganan melalui citra merek. Hasil penelitian menunjukkan bahwa citra merek secara positif dan signifikan memperkuat pengaruh eWOM terhadap keputusan berlangganan.Kata kunci: citra merek; e-WOM; Instagram; Keputusan Berlangganan; Netflix